DESIGN OF ACCOUNTING INFORMATION SYSTEM FOR PRODUCTION CYCLE USING ACCURATE ACCOUNTING SOFTWARE TO INCREASE INTERNAL CONTROL IN “X” FIRM - Sadlin, Cindy; Wirawan, Adhicipta R. (University of Surabaya, 2013)
This research has purpose to design accounting information system for production cycle in small manufacturing firm that does not run computerized system. As small firm is the starting point of a bigger firm, the design of accounting information system needs to be considered, especially for the internal control. In manufacturing firm, when the internal control has been properly conducted, the production operation effectiveness and efficiency can be achieved. In designing new accounting information system, qualitative approach is used for this research. Besides, accounting software that supports manufacturing module is very helful to design the accounting information system. As the result, design of accounting information system for production cycle in “X” firm uses Accurate accounting software.